The Effectiveness of Blended Learning For Undergraduate Nursing Students: A Systematic Review - Tarigan, Yohanes Zenriano; Kusumaningtyas, Dwi Prima Hanis; Simanjuntak, Therecia (Babali Nursing Research, 2025)
Introduction: Implementing conventional and online learning is considered insufficient to balance current educational needs, so blended learning is needed, combining the two learning methods to include more comprehensive learning. This study aims to systematically investigate the literature regarding the effectiveness of blended learning for undergraduate nursing students in Indonesia. Methods: Systematic review by searching articles using CINAHL, PubMed, Science Direct, ProQuest, SINTA, GARUDA, manual search, and electronic search engine "Google Scholar," with full-text article criteria, articles that have been published since Blended Learning was carried out for nursing students using Indonesian and English articles, the keywords used are Nursing student, blended learning, the effectiveness of blended learning. The research design included a Randomized Controlled Trial (RCT) and a Quasi-Experimental Study. Results: A total of 15 research articles, a Randomized Controlled Trial (RCT), A qualitative study, and a Quasi-Experimental Study that met the eligibility criteria, and all showed that blended learning can significantly help nursing student learning, including knowledge, clinical practice skills, learning content and instruction, learning reflection, and learning information media. There are differences in the results found from the use of media and learning materials provided and used. Conclusion: Conclusion: Blended learning can be used as a learning reference because it is considered effective in carrying out the learning process in nursing.